Association of IFN-γ T/A +874 Gene Polymorphism with Type-1 diabetes mellitus in Iraqi Children (Texas Journal of Medical Science, 2023)
The purpose of this case-control study was to examine the association between polymorphisms in the IFN-γ T/A +874 Gene Polymorphism and the development of Type 1 Diabetes mellitus. Samples of blood were taken from 60 people with Type 1 diabetes mellliuts and 40 healthy controls for this study serum levels were found to be significantly higher (p>0.05) than healthy. The frequency of the allele and genotypes in the patient groups and control groups were determined using Allele Specific-PCR, Triiodothyronine (T3), Thyroxine (ng/ml), and Thyroid Stimulating Hormone (mU/L) levels in the blood were measured using a kit designed to do so in accordance with the manufacturer's instructions. The study show a significant (p ≤ 0.05) increase in TSH in Patient subjects (diabetic mellitus ) as compared to the control group as shown in table (4-2) and this result is in agreements with. The study also shown that there is a significant (p ≤ 0.05) increase in both hormones ( T3& T4 ) n the P atient subjects (diabetic mellitus ) when compared to the control group. In the current study liver enzyme (AST, ALP& ALT) shown a significant (p ≤ 0.05) increase in Patient subjects (diabetic mellitus) as compared to the control. Patients had an increased frequency of the TT homozygous and TA heterozygous genotypes compared to controls (15 vs. 22 and 21 vs. 12) respectivelly. When comparing the odds ratios (OR) of 0.38 (95% CI: 0.148 to 1.024) and 1.71 (95% CI: 0.05 to 0.51) for the two groups, with statistically significant difference (p = 0.0539 and P=0.0042) respectively. Patients also had a much higher frequency of the (A) allele than controls did (34.5 vs. 12, OR = 0.327, 95% CI = 0.14 to 0.76, p = 0.009).